Circulating miR-28-5p is overexpressed in patients with sarcopenia despite long-term remission of Cushing’s syndrome: a pilot study - Seco-Cervera, Marta; Ibáñez-Cabellos, José Santiago; Pallardo, Federico V.; García-Giménez, José-Luis; Aulinas, Anna; Martel-Duguech, Luciana; Webb, Susan M.; Valassi, Elena (Frontiers in Endocrinology, 2024)
Introduction: Patients with Cushing's syndrome (CS) in remission show sustained fatigue, myopathy, and an increased prevalence of sarcopenia. The mechanisms that determine these persistent muscle problems are not well known. We aimed to identify circulating microRNAs (miRNAs) with differential expression that could be potential biomarkers for the diagnosis and/or prognosis in CS.Patients and methods: Thirty-six women in sustained remission for 13 + 7 years (mean±SD) from CS, with a median age (IQ range) of 51 (45.2-60) years and mean±SD BMI of 27±4 Kg/m 2 , and 36 matched healthy controls were investigated. In 7 patients sarcopenia was present according to the European Working Group on Sarcopenia in Older People (EWGSOP) criteria. Small RNA libraries were generated and indexed using a modified Illumina TruSeq small RNA-sequencing protocol. MiRNAs were identified in plasma using bioinformatic analysis, and validation was carried out using RT-qPCR. For the validation, Taqman probes were performed on QuantStudio 5 equipment (Applied Biosystems).Results: In a first discovery group using RNA-sequencing, plasma samples of 18 CS patients and 18 healthy subjects were investigated; circulating miR-28-5p, miR-495-3p and miR-654-5p were upregulated in CS patients as compared with controls (p<0.05). In a validation study of the 3 upregulated miRNAs in 36 patients and 26 controls, no differences were observed by RT-qPCR; however, the expression of circulating miR-28-5p was upregulated in CS patients with sarcopenia as compared with those without (AUC for fold-change in the ROC analysis, 0.798; p=0.0156). The optimized cut-off value for miR-28-5p to identify CS patients with sarcopenia was 3.80, which yielded a sensitivity of 86 % and a specificity of 69 %.Conclusion: MiR-28-5p, a muscle-specific microRNA involved in myotube proliferation and differentiation in vivo, may serve as an independent non-invasive biomarker for identifying CS patients at high-risk of sarcopenia despite biochemical remission.